Supplemental Vitamins and Minerals for CVD Prevention and Treatment - Jenkins, David J A; Spence, J David; Giovannucci, Edward L; Kim, Young-In; Josse, Robert; Vieth, Reinhold; Blanco Mejia, Sonia; Viguiliouk, Effie; Nishi, Stephanie; Sahye-Pudaruth, Sandhya; Paquette, Melanie; Patel, Darshna; et al. (Journal of the American College of Cardiology, 2018)
The authors identified individual randomized controlled trials from previous meta-analyses and additional searches, and then performed meta-analyses on cardiovascular disease outcomes and all-cause mortality. The authors assessed publications from 2012, both before and including the U.S. Preventive Service Task Force review. Their systematic reviews and meta-analyses showed generally moderate- or low-quality evidence for preventive benefits (folic acid for total cardiovascular disease, folic acid and B-vitamins for stroke), no effect (multivitamins, vitamins C, D, β-carotene, calcium, and selenium), or increased risk (antioxidant mixtures and niacin [with a statin] for all-cause mortality). Conclusive evidence for the benefit of any supplement across all dietary backgrounds (including deficiency and sufficiency) was not demonstrated; therefore, any benefits seen must be balanced against possible risks.